Annual Research Review: Threats to the validity of child psychiatry and psychology. (19th September 2015) - Rutter, Michael; Pickles, Andrew
Abstract : Background: Suggestions have been made that many claims concern false‐positive findings in the field of child psychology and psychiatry. Findings: The literature was searched for concepts and findings on the validity of child psychiatry and psychology. Substantial progress has been made in some, but not all, areas and considerable challenges remain in all. Conclusions: The two major threats to validity concern the inability to examine brain tissues in life and the evidence that there is a high overlap among disorders. We emphasize the need to follow published guidelines on preplanned analyses and we note the dangers associated with unregulated flexibility in data analysis. We note the very important clinical and developmental findings that have been ignored, perhaps partly because of an excessive focus on technologies. Nevertheless, we are positive about both the accomplishments and the ways in which challenges are being met. Abstract : Read the Commentary on this article at doi:10.1111/jcpp.12541